Analysis Of Factors Affecting Facility Management At Jati Kudus Terminal - Leksana, Radhitya Arby Putra; Syafiul, Muhammad Tsani; Rizani, Mohammad Debby (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2026)
Jati Kudus Terminal is a type A terminal that plays an important role in land transportation services. The quality of facility management significantly affects service effectiveness and user comfort. This study aims to identify factors influencing facility management at Jati Kudus Terminal. The research uses a quantitative descriptive approach with data collected through observation, interviews, documentation, and questionnaires. The analysis focuses on identifying key influencing factors based on service standards. The results show that facility management is influenced by six main factors: safety, security, reliability, comfort, accessibility, and equality. These factors determine the effectiveness of terminal services and require continuous evaluation for improvement.